(3Pjd dH GddHGH ddSjhWis - (3CMeO GdYLejs ((3YHO GdQMef GdCTehfi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO ajbhd GdabjQ Edi Gddg JYGdi YHO GdQMef GdCTehfi (B: (3gPG eG LQOJg ef NW TjNfG CMeO GdYLei ef gGeT fSNJg dH GddHGH s
(3BNQgG (B:s
(3bQjI HYjdHc hCNQi Hjf HQOYI hHjdbGf ajMJed Cfg efShH Edi CMOgeG TPhPG , hGdbjGS (B: (3jhfGfi (B: (3hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(277(3b(B) s
Keywords: (3GdJGQjNs